2014
DOI: 10.1037/a0034683
|View full text |Cite
|
Sign up to set email alerts
|

When boys wear pink: A gendered color cue violation evokes risk taking.

Abstract: A primary way to signal gender differences starting in infancy is via a clothing color cue (pink is for girls, not boys). We examined whether a violation of this seemingly innocuous gendered prescription would lead to differential decision making regarding infants' health and well being. In Experiment 1, partici pants were given an adaptation of the Asian Disease Problem (Tversky & Kahneman, 1981) describing a flu outbreak expected to affect male infants, who were dressed in pink or blue. Participants tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Martin () suggested that in the case of conscious awareness, people try to remove the influence of priming on the basis of judgment in order to make an appropriate judgment. In fact, a recent study showed that wearing pink clothes among boys evoked masculine behavior (i.e., risk taking) because men's pink clothing violated traditional gender roles (Ben‐Zeev & Dennehy, ). Male participants might be conscious of wearing pink clothes, which are counter‐stereotypical and unfamiliar for them.…”
Section: Discussionmentioning
confidence: 99%
“…Martin () suggested that in the case of conscious awareness, people try to remove the influence of priming on the basis of judgment in order to make an appropriate judgment. In fact, a recent study showed that wearing pink clothes among boys evoked masculine behavior (i.e., risk taking) because men's pink clothing violated traditional gender roles (Ben‐Zeev & Dennehy, ). Male participants might be conscious of wearing pink clothes, which are counter‐stereotypical and unfamiliar for them.…”
Section: Discussionmentioning
confidence: 99%
“…A gender–color interference effect was observed in pink–masculine condition but not in blue–feminine condition, suggesting that pink, but not blue, is a gender identity-related color in Chinese culture. Notably, participants in many Western societies usually treat pink as a feminine color and blue as a masculine color ( Bargh, 1999 ; Macrae and Bodenhausen, 2000 ; Ben-Zeev and Dennehy, 2014 ). However, a recent study on Swiss participants’ color preference showed that, while pink was favored only by female participants, blue was favored equally by both genders, regardless of age ( Jonauskaite et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in Western culture, girls are often dressed in pink, while boys are often dressed in blue ( Pomerleau et al, 1990 ). These gender–color associations have emerged in the Western world since the 1950s ( Frassanito and Pettorini, 2008 ; Ben-Zeev and Dennehy, 2014 ; Grisard, 2018 ), and such color preference differences between the two genders may extend from childhood to adulthood (e.g., Cunningham and Macrae, 2011 ). Nevertheless, a recent study demonstrated, at least in some Western societies, that pink is a color restricted to female gender (i.e., only girls prefer pink), whereas blue is a neutral color that is commonly favored by both genders; such female gender preference toward pink was found in children as young as 10 years old ( Jonauskaite et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…People who violate gender norms experience gender backlash (Rudman, 1998). A male associated with pink might be perceived as gender non‐normative due to pink's diagnostic meaning of gender and thus be perceived as socially deviant (Ben‐Zeev & Dennehy, ). Research suggests that as of age 2, boys show avoidant behavior toward pink (LoBue & DeLoache, ).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from metaphors linking pink and optimism, pink is also associated with gender—namely, femininity (e.g., Ben‐Zeev & Dennehy, ; Weisgram, Fulcher, & Dinella, ). LoBue and DeLoache () noted that “it is thus clear, both from everyday observation and from research results, that both adults and young children are aware that pink is for girls and blue is for boys” (p. 657).…”
Section: Optimism and Pink Metaphorsmentioning
confidence: 99%